2004
DOI: 10.1128/jcm.42.6.2602-2608.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Tuberculosis ( Mycobacterium bovis ) in Wildlife in Spain

Abstract: Mycobacterium bovis infection in wildlife and feral species is a potential source of infection for livestock and a threat to protected and endangered species. The aim of this study was to identify Spanish wild animal species infected with M. bovis through bacteriological culture and spacer oligonucleotide typing (spoligotyping) of isolates for epidemiological purposes. This study included samples from red deer (Cervus elaphus), fallow deer (Dama dama), wild boar (Sus scrofa), Iberian lynx (Lynx pardina), hare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(157 citation statements)
references
References 41 publications
(37 reference statements)
5
145
1
4
Order By: Relevance
“…This suggests that wild ungulates may be maintenance hosts of M. bovis in Portugal, because if they were spillover hosts and the infection was maintained primarily by cattle, we would not expect the occurrence of M. bovis to be linked with their density, but rather with cattle variables. Others already have suggested that the wild boar is a maintenance host of M. bovis in Iberian Peninsula Mediterranean habitats (Aranaz et al, 2004;Vicente et al, 2006), and our data support their hypothesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that wild ungulates may be maintenance hosts of M. bovis in Portugal, because if they were spillover hosts and the infection was maintained primarily by cattle, we would not expect the occurrence of M. bovis to be linked with their density, but rather with cattle variables. Others already have suggested that the wild boar is a maintenance host of M. bovis in Iberian Peninsula Mediterranean habitats (Aranaz et al, 2004;Vicente et al, 2006), and our data support their hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Isolation rates for M. bovis were 6, 22, and 46% in tuberculosisinfected areas. In this study, as well as in the study by Aranaz et al (2004), M. bovis infection rates in wild boar were estimated by systematically employing bacteriology and not relying on gross pathology as the screening test. This is of relevance because gross pathology alone can substantially underestimate disease prevalence, as shown in free-ranging cervids (O'Brien et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…M. bovis can also infect a wide range of domestic and wild animals [21,25] and some of them are considered as reservoirs of infection for livestock. The risk these reservoirs constitute for domestic animals depends on the specific epidemiological situation of the species and the environment [21] and has been demonstrated under a similar situation in Spain [1].…”
Section: Discussionmentioning
confidence: 91%
“…The biotin-labelled amplified product was hybridised onto a membrane (Isogen Bioscience BV, Maarssen, The Netherlands) and detected with the streptavidin-peroxidase conjugate (Roche Diagnostics GmbH, Penzberg, Germany) and the ECL system (Amersham Biosciences UK Ltd., Buckinghamshire, UK). A part of these results have been published previously [1].…”
Section: Molecular Characterisation Of M Bovis Isolatesmentioning
confidence: 95%
“…However, there is a generally higher risk and uncertainty associated with bTB levels in deer, including roe deer (Capreolus capreolus), red deer (Cervus elaphus), fallow deer (Dama dama) and muntjac (Muntiacus reevesi) [42]. Deer have been implicated as a wildlife source for bTB in other parts of the world [43][44][45][46], so bTB infection in the British farmland ecosystem could also be assisted by the presence of deer within the host community in certain areas. However, an assessment of the potential additional risk from deer is reliant on knowledge of the spatial distribution and abundance of the principal wildlife host, the badger, which has generally been the limiting factor in landscape-scale analyses of bTB incidence [24][25][26]47].…”
Section: Spread Of Btb Across Landscapes and Within Ecosystemsmentioning
confidence: 99%